2017
DOI: 10.1016/j.jtcme.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and medication characteristics of traditional Chinese medicine users among colorectal cancer survivors: A nationwide database study in Taiwan

Abstract: Chinese herbal product (CHP) is the major type of traditional Chinese medicine (TCM) and widely used to relief the symptom of colorectal cancer. The aim of the study was to analyze the utilization of CHP for treating patients with colorectal cancer in Taiwan. The usage of CHP, frequency of services, and prescription pattern for colorectal cancer were analyzed from a randomly sampled cohort of 1 million beneficiaries from the National Health Insurance Research Database. The odds ratios for utilization of CHP we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…HCC remains among the leading cause of cancer-related death worldwide [ 47 , 48 ]. Although therapeutic approaches for advanced HCC are limited to the use of multikinase inhibitors, such as sorafenib, only modest survival benefits have clinically been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HCC remains among the leading cause of cancer-related death worldwide [ 47 , 48 ]. Although therapeutic approaches for advanced HCC are limited to the use of multikinase inhibitors, such as sorafenib, only modest survival benefits have clinically been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Although therapeutic approaches for advanced HCC are limited to the use of multikinase inhibitors, such as sorafenib, only modest survival benefits have clinically been reported. Thus, identifying new compounds with promise antitumor activity against HCC is exceedingly needed [ 48 , 49 ]. Natural products, especially from plants, are often better tolerated than their synthetic analogs used in cancer treatments [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cinobufagin, another cardiotonic steroid isolated from Chan Su, suppresses tumor neovascularization by disrupting the endothelial mTOR/HIF-1α pathway to trigger reactive oxygen species-mediated vascular endothelial cell apoptosis (Li et al, 2019). Of the frequently used TCM treatments, the most effective single herbs are Ginseng Radix (Ren Shen), Hedyotis diffusa Willd (Bai Hua She She Cao), Scutellaria barbata (Ban Zhi Lian), and Astragali Radix (Huang Qi) (Lee et al, 2014;Wu et al, 2017). However, the underlying mechanisms of these remedies remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…FYY contains eight herbs: Astragali Radix (Huang Qi), Ganoderma lucidum (Ling Zhi), Semen Armeniacae Amarum (Ku Xing Ren), H. diffusa Willd (Bai Hua She She Cao), Aconiti Lateralis Radix Praeparata (Fu Zi), Glycyrrhiza glabra Linne (Gan Cao), Radix Panacis Quinquefolii (Xi Yang Shen), and Platycodi Radix (Jie Geng). Of these herbs, Radix Panacis Quinquefolii (Ginseng Radix), H. diffusa Willd, and Astragali Radix are commonly used in anticancer formulas (Lee et al, 2014;Wu et al, 2017). G. lucidum and Platycodi Radix also reportedly have anticancer effects; Radix Astragali (Jung et al, 2016), G. lucidum (Dai et al, 2014), Platycodi Radix (Park and Lee, 2014), and H. diffusa Willd (Zhang et al, 2016) inhibit cancer cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…It is now widely accepted and employed for the integrative management of CRC and other malignancies in China. [11][12][13][14][15] Moreover, evidence-based investigations have revealed that CHM plays a significant role in tumorigenesis, reduction of toxicity, increased treatment effect, and decreased risk for CRC recurrence and metastasis. [16][17][18] Furthermore, a prospective multicenter study 19 of 312 patients who had received comprehensive conventional treatments examined the relationship between CHM therapy and survival outcomes.…”
Section: Introductionmentioning
confidence: 99%